Potatoes on my Head: A Stem Based Learning Model for 2nd Grade Elementary Students - Sasriyanti, Rika; Munawir, Munawir; Aosi, Ghenny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Education in the age of the industrial revolution 4.0 requires teachers to become innovative; teachers need to be able to adapt science and technology innovations to learning trends in the classroom. Science, Technology, Engineering, and Mathematics (STEM) approach is an alternative learning approach that allows students to have the complete skills desired by 21st century learning. Utilizing the STEM approach in a learning environment allows several topics to be effectively learned in a grade II elementary classroom. One STEM approach used ‘Potatoes in My Head’, has learners learn about food ingredients, using measuring instruments, as well as basic techniques of engineering. This paper is the result of best practices carried out by the teacher in the second semester of the 2018/2019 academic year and involved 29 second grade students at a public elementary school in Bukittinggi, Indonesia. The aim is to see the improvement of students’ learning outcomes and critical thinking skills. The knowledge was gathered through observation strategies and assessments of learning outcomes. The findings showed that the STEM approach in the Potatoes in My Head operation helped enhance learning outcomes and the students’ critical thinking skills.